2019
DOI: 10.1002/jsp2.1074
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biomechanical effects of annulus fibrosus injury and repair in an ovine cervical model

Abstract: Tissue engineering repair of annulus fibrosus (AF) defects has the potential to prevent disability and pain from intervertebral disc (IVD) herniation and its progression to degeneration. Clinical translation of AF repair methods requires assessment in long‐term large animal models. An ovine AF injury model was developed using cervical spinal levels and a biopsy‐type AF defect to assess composite tissue engineering repair in 1‐month and 12‐month studies. The repair used a fibrin hydrogel crosslinked with genipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…The cytotoxicity findings were supported by studies done in vitro. 40,42 On the other hand, it is in contradiction with some previously published work which showed no effect on cell viability in ex vivo organ cultures 21 and in vivo, 57 although the exact recipes for the FibGen hydrogel vary between the studies, as well as the geometry of the injury and the repair. shown to promote cell infiltration and effectively seal AF defects in small animal models in vivo and restore some aspects of biomechanics.…”
Section: Mechanical and Biological Evaluation Of The Endplate Delammentioning
confidence: 57%
See 3 more Smart Citations
“…The cytotoxicity findings were supported by studies done in vitro. 40,42 On the other hand, it is in contradiction with some previously published work which showed no effect on cell viability in ex vivo organ cultures 21 and in vivo, 57 although the exact recipes for the FibGen hydrogel vary between the studies, as well as the geometry of the injury and the repair. shown to promote cell infiltration and effectively seal AF defects in small animal models in vivo and restore some aspects of biomechanics.…”
Section: Mechanical and Biological Evaluation Of The Endplate Delammentioning
confidence: 57%
“…If, however, free genipin molecules are an issue, in vivo environment would provide more continuous motion and fluid exchange, which could potentially further reduce the effect of the genipin. This assumption is supported by in vivo study by Long et al which showed no long-term cytotoxic or inflammatory effect from genipin in ovine IVDs 57. In the latter more likely case, the reinforcing effect would stand in direct contradiction with cell survival.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Despite intense research interest, attempts to regenerate the IVD have failed so far and no effective strategy has translated into a successful clinical outcome [ 24 , 25 ]. Of particular significance, the failure of strategies to repair the AF has been a major drawback in the regeneration of IVD and nucleus replacement [ 26 ]. Since IVD is exposed to significant load and large deformation during daily activities, it is unlikely to secure regenerative mediators (cells, genes, and biomolecules) and artificial nucleus materials after injection into a herniated IVD.…”
Section: Introductionmentioning
confidence: 99%